Theoretical Aspects of some Mechanical Properties of Composites - Sabah S. AbdulNoor; Ahmad Al-Beiruti; Mustafa Nashat (Engineering and Technology Journal, 2010)
In the present wok, two mathematical models are constructed in orderto define the detailed nature of composite. The first one is based on theclassical Rule of Mixtures, (RoM) which is normally rotted from the ordinarystrength of materials. The second model is based on the theory of elasticity,which deals with the detailed response of the internal macrostructure of thecomposite. A virtual composite was assumed to be formed of a number ofmatrices (Epoxy resin & Nickel) containing various inclusions (Carbon fibres& powder, E-glass fibres & powder, and Kevlar fibres) in sequentialpermutations. In general, the elasticity model E, exhibited various degrees ofsuperiority to the RoM depending on the mechanical parameters in questionand the mechanism by which it influences the internal details of the material.